An An Investigation of Gender Equality Represented in Indonesian Junior High School EFL Textbook - Nurkarimah; Dihliza Basya; Moh. Arif Mahbub (Linguapedia, 2025)
Gender issue has become a topic of numerous studies in educational field. However, the availability of texbooks that representing gender equality are still limited. Thus urges textbook designers become aware in accomodating gender equality in EFL textbook. To fill this gap, the present study aims to investigate gender equality in Indonesian EFL textbook mandated for Junior High School grade IX. Adopting content analysis as research design, the content of textbook including multimodal texts, verbal and visual texts were analyzed by researcher. Gender neutral vocabularies, a balance proposition male and female vocabularies, the frequency of male’s and female’s visibility throughout images in the textbook were found to construct gender equality represented in the textbook. The finding show that the textbook designers are aware to minimize gender inequality represented in EFL textbook. Finally the implication of present study is English teacher and textbook designers should be fully aware and pay attention more about gender equality depicted in EFL textbook.